MANAJEMEN KINERJA DAN KINERJA ORGANISASI: TINJAUAN SISTEMATIS - Wirtadipura, Dian; Kurniasih, Dedeh; Tajudin, Tajudin (DESANTA (Indonesian of Interdisciplinary Journal), 2025)
This study aims to synthesize scientific literature on the relationship between performance management and organizational performance through a systematic literature review approach to four scientific articles published between 2019 and 2024. This study shows that the effectiveness of a performance management system is not universal, but rather highly dependent on the organizational context, system integration, and mediating and moderating factors. The results of the thematic analysis reveal that effective performance management practices not only improve internal process efficiency but also strengthen strategic adaptation and organizational innovation. Key findings include the mediating role of performance management in linking managerial innovation to organizational performance, the synergy between corporate performance management and business process management, and the importance of integrating business intelligence and analytics in the public sector. In addition, this study highlights environmental uncertainty as a critical moderator in the design of an adaptive performance management system. This study provides conceptual contributions by strengthening the theory of resource-based view, resource orchestration, and contingency theory, as well as practical contributions in the form of recommendations for developing a contextual, data-based, and collaborative performance management system. The implications of this study are an important foundation in designing strategic policies for managing organizational performance that are more responsive to VUCA challenges.